The Effect of Using the Problem-Based Learning (PBL) Model on Students' Critical Thinking Skills in Science Learning: A Literature Review - Dewi, Lusiana Nofita; Wahyuni, Sri; Barid, Siti Shofa Assyifa’ul Qulbi; Astuti, Sri Rejeki Dwi (Jurnal Simki Pedagogia, 2026)
The level of critical thinking skills among students in science education is still relatively low because the learning models used have not been able to optimize their thinking processes, which are still teacher-centered and lack meaningful problem-solving experiences. This study aims to analyze the impact of the PBL model in improving students' critical thinking skills by applying the Systematic Literature Review method in accordance with the PRISMA guidelines. This research method identified 781 articles through Google Scholar, of which 22 articles met the inclusion criteria. The results show that PBL effectively optimizes students' higher-order thinking skills by involving them in contextual learning. PBL also provides more structured opportunities for scientific reasoning compared to other models. Further research is recommended to analyze the integration of PBL with various other digital media that can explore long-term impacts and involve broader levels of education for more comprehensive results.